Pembelajaran Melalui Pendekatan Pendidikan Matematika Realistik Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa SMP - Destiana Mali , Maria; Loka Son, Aloisius (Hexagon: Jurnal Ilmu dan Pendidikan Matematika, 2023)
This study was conducted with the aim of determining the comparison of achievement and improvement in the problem-solving ability of students who learn through realistic mathematics education and a conventional approach. The study used quantitative methods in the form of a quasi-experiment. The design of this study used a pretest-posttest control group design. The participants in this study were students in grade VIII from one of the junior high schools in the Belu district. The sample in this study consisted of 22 students from class VIIIA as the experimental group, and 22 students from class VIIIB as the control group. The research instruments used were a problem-solving ability test and observation sheets. The results showed that the achievement and improvement in the mathematics problem-solving ability of students who learned through the realistic mathematics education approach were better than those of students who learned with a conventional approach. Learning with a realistic mathematics education approach can facilitate the problem-solving skills of junior high school students. It is recommended that future researchers apply the realistic mathematics education approach to other mathematical abilities.